A Meta-Analysis of Nonpharmacological Interventions for People With Parkinson's Disease. (October 2017) - Lee, JuHee; Choi, MoonKi; Yoo, Yonju
Nonpharmacological interventions are important in providing care for Parkinson's disease (PD) patients. However, there is limited evidence related to their impacts on health-related quality of life (HRQOL). We aimed to examine the effectiveness of nonpharmacological interventions for improving the HRQOL of PD patients. Articles published in peer-reviewed journals from 2000 to 2015 were searched through electronic searching, computerized author searching, and footnote chasing. A meta-analysis was performed using the RevMan 5.3 program. Overall, effect size for the studies ( n = 18) was −4.17 with 95% confidence interval (CI) from −7.63 to −0.70 ( Z = 2.36, p = .02), indicating positive effects of nonpharmacological interventions on HRQOL. In subgroup analysis regarding the intervention types, the effect size of exercise programs was −5.73 with 95% CI of −11.36 to −0.10 ( Z = 2.00, p = .05). Thus, nonpharmacological interventions, and particularly exercise programs, were effective in improving the HRQOL of PD patients.